An introduction to ACAS Xu and the challenges ahead - Manfredi, Guido; Jestin, Yannick (IEEE/AIAA Digital Avionics Systems Conference, 2016)
According to a 2013 AUVSI report, delays in integrating Unmanned Aerial Systems (UAS) into the National Airspace System (NAS) could cost more than 10 billions a year for the United States alone. Worldwide regulatory bodies are under pressure by the UAS industry to accelerate the regulation process, but safety remains their main objective. One condition for the safe introduction of UAS in the NAS is for them to be equipped with a collision avoidance system. Though the existing Airborne Collision Avoidance System II (ACAS II) could have been an option, the transformations of air traffic management engaged through NextGen (US) and SESAR (Europe) led to the definition of a new ACAS based on new logics, namely ACAS X. Its definition contains in particular two variations : ACAS Xa, for large aircraft, and ACAS Xu, for unmanned aircraft. As noted in a 2014 RTCA annual report, divide in technological knowledge between those experienced in ACAS II and those involved in the development of ACAS X is a concern. To help preventing this divide we believe it is essential to keep the community updated with the latest evolutions of the ACAS X standards. As work on Minimum Operational Performance Standards (MOPS) for ACAS Xu just started, it is of interest to know which parts of the MOPS are already decided, which remain flexible for the industries to make the difference and which are open research problems. Being a member of the ACAS X family, ACAS Xu lays on the same foundations as the well defined ACAS Xa standard. This work proposes an introduction to the ACAS Xa/Xu common basis, as it is unlikely to change, including the general architecture and Collision Avoidance (CA) logics. It is followed by a presentation of concepts specific to ACAS Xu such as the tailored threat logic, horizontal CA logic, CA coordination and automatic responses. For the flexible part, we believe it mainly concerns the surveillance sources. Instead of a precise standard, the regulation is likely to ask for requirements on the sensors capabilities. A state of the art of recent works allows proposing minimum sensor performances and focusing on an essential set of sensors. This work is concluded by presenting future challenges that need to be addressed to build a safe ACAS Xu baseline and to extend it to smaller and lower altitude UAS.